Isolation of basal membrane proteins from BeWo cells and their expression in placentas from fetal growth-restricted pregnancies. (March 2016) - Oh, Soo-young; Hwang, Jae Ryoung; Lee, Yoonna; Choi, Suk-Joo; Kim, Jung-Sun; Kim, Jong-Hwa; Sadovsky, Yoel; Roh, Cheong-Rae
Abstract: Introduction: The syncytiotrophoblast, a key barrier between the mother and fetus, is a polarized epithelium composed of a microvillus and basal membrane (BM). We sought to characterize BM proteins of BeWo cells in relation to hypoxia and to investigate their expression in placentas from pregnancies complicated by fetal growth restriction (FGR). Methods: We isolated the BM fraction of BeWo cells by the cationic colloidal silica method and identified proteins enriched in this fraction by mass spectrometry. We evaluated the effect of hypoxia on the expression and intracellular localization of identified proteins and compared their expression in BM fractions of FGR placentas to those from normal pregnancies. Results: We identified BM proteins from BeWo cells. Among BM proteins, we further characterized heme oxygenase-1 (HO-1), voltage-dependent anion channel-1 (VDAC1), and ribophorin II (RPN2), based on their relevance to placental biology. Hypoxia enhanced the localization of these proteins to the BM of BeWo cells. HO-1, VDAC1, and RPN2 were selectively expressed in the human placental BM fraction. C-terminally truncated HO-1 was identified in placental BM fractions, and its BM expression was significantly reduced in FGR placentas than in normal placentas. Interestingly, a truncated HO-1 construct was predominantly localized in the BM in response to hypoxia and co-localized with VDAC1 in BeWo cells. Discussion: Hypoxia increased the BM localization of HO-1, VDAC1, and RPN2 proteins. FGR significantly reduced the expression of truncated HO-1, which was surmised to co-localize with VDAC1 in hypoxic BeWo cells. Highlights: We isolated the basal membrane from BeWo cells using the cationic colloidal silica method. HO-1, VDAC1, and RPN2 proteins were identified as basal membrane proteins. Hypoxia increased the membranous localization of HO-1, VDAC1, and RPN2 proteins. Truncated HO-1 was expressed in the basal membrane fraction of human placenta. FGR significantly reduced the expression of truncated HO-1.